Changes in Dynamic Strength Index in Response to Strength Training - Paul Comfort; Christopher Thomas; Thomas Dos'Santos; Timothy J. Suchomel; Paul A. Jones; John J. McMahon (MDPI AG, 2018)
The primary aim of this investigation was to determine the effects of a four-week period of in-season strength training on the dynamic strength index (DSI). Pre and post a four-week period of strength-based training, twenty-four collegiate athletes (age = 19.9 ± 1.3 years; height = 1.70 ± 0.11 m; weight 68.1 ± 11.8 kg) performed three isometric mid-thigh pulls and countermovement jumps to permit the calculation of DSI. T-tests and Cohen’s effect sizes revealed a significant but small (p = 0.009, d = 0.50) decrease in DSI post-training (0.71 ± 0.13 N·N−1) compared to pre-training (0.65 ± 0.11 N·N−1); however, when divided into high and low DSI groups, differential responses were clear. The low DSI group exhibited no significant or meaningful (p = 1.000, d = 0.00) change in DSI pre to post-training (0.56 ± 0.05 N·N−1, 0.56 ± 0.09 N·N−1, respectively), whereas the high DSI group demonstrated a significant and large decrease (p = 0.034, d = 1.29) in DSI pre to post-training (0.85 ± 0.05 N·N−1, 0.74 ± 0.11 N·N−1, respectively), resulting in a significant and moderate difference (p = 0.034, d = 1.29) in the change in DSI between groups. These results demonstrate that DSI decreases in response to strength training, as expected, due to an increase in isometric mid-thigh pull peak force, with minimal change in dynamic (countermovement jump) peak force.